2019
DOI: 10.1029/2018jc014604
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Pacific Winter Water in the Western Arctic Ocean

Abstract: Pacific Winter Water (PWW) enters the western Arctic Ocean from the Chukchi Sea; however, the physical mechanisms that regulate its circulation within the deep basin are still not clear. Here, we investigate the interannual variability of PWW with a comprehensive data set over a decade. We quantify the thickening and expansion of the PWW layer during 2002–2016, as well as its changing pathway. The total volume of PWW in the Beaufort Gyre (BG) region is estimated to have increased from 3.48 ± 0.04 × 1014 m3 dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 62 publications
9
39
1
Order By: Relevance
“…This explanation is in agreement with seasonal changes of freshwater content below 65 m observed in the mooring data where maximum freshwater content was observed in January–February and minimum in June–July when wind‐driven downwelling in the southwest Canada Basin/Chukchi Sea is replaced by upwelling. Zhong et al (, this special issue) investigated changes in the Pacific winter water located between the Pacific summer and Atlantic water layers and showed that under the influence of Ekman pumping and lateral advection, the thickness and freshwater content of this layer increased by approximately 18% over the years 2002–2016.…”
Section: Freshwater Content Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This explanation is in agreement with seasonal changes of freshwater content below 65 m observed in the mooring data where maximum freshwater content was observed in January–February and minimum in June–July when wind‐driven downwelling in the southwest Canada Basin/Chukchi Sea is replaced by upwelling. Zhong et al (, this special issue) investigated changes in the Pacific winter water located between the Pacific summer and Atlantic water layers and showed that under the influence of Ekman pumping and lateral advection, the thickness and freshwater content of this layer increased by approximately 18% over the years 2002–2016.…”
Section: Freshwater Content Variabilitymentioning
confidence: 99%
“…This explanation is in agreement with seasonal changes of freshwater content below 65 m observed in the mooring data where maximum freshwater content was observed in January-February and minimum in June-July when wind-driven downwelling in the southwest Canada Basin/Chukchi Sea is replaced by upwelling. Zhong et al (2019, (Steele et al, 2001;Serreze et al, 2006;Timokhov & Tanis, 1997. Instead, the observations indicated that over 2003-2008, there were two seasonal maxima in freshwater content; one in June-July when sea ice thickness reached its minimum (maximum ice melt) and the second in November-January when Ekman pumping was strongest and salt input from ice growth had not yet reached its maximum.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 99%
“…Kelly, Popova, Aksenov, et al, () employ the use of tracers in the Coupled Model Intercomparison Project Phase 5 (CMIP5) model to ascertain Arctic Ocean pathways of pollutants from Siberian Rivers. Thickening, expansion, and redistribution of the Pacific Winter Water layer are quantified by Zhong et al (). Shu et al () investigate future changes of freshwater content under influence of different factors including circulation changes in the future.…”
Section: Beaufort Gyre Phenomenon: Multicomponent System Mechanisms Amentioning
confidence: 99%
“…Aksenov et al, 2016;Jones, 2001;McLaughlin et al, 2002;Steele et al, 2004;Timmermans et al, 2014). In this special collection, Spall et al (2018), Zhong et al (2019), Hirano et al (2018), and Hu and Myers (2019) discuss the most recent findings associated with the circulation of the Pacific water layers and factors influencing their dynamics and properties.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, it is not possible, from our ITP data, to conclude whether the strength of vertical mixing at the mixed layer base changed over 2006-2017. Beyond the conclusion that vertical mixing is not the sole cause of increased mixed layer salinity, the exact mechanism can only be speculated on from these observations. It is possible that the stabilization of the Beaufort Gyre documented in recent studies led to increased mixed layer salinities via a reduced Ekman convergence of freshwater (Dewey et al, 2018;Meneghello et al, 2018;Zhang et al, 2016;Zhong et al, 2018), which made it easier for the "background" level of mechanical mixing to deepen the mixed layer base. Alternatively, the increased mixed layer salinity could have resulted from a net export of freshwater out of the Beaufort Gyre, implying that the Arctic Ocean could increase freshwater export to the North Atlantic should these conditions continue.…”
Section: Causes Of a Deeper Saltier And Denser Winter Mixed Layermentioning
confidence: 99%